Supervisors’ Possession of Supervisory Skills - Al-Ghazal, Mohammed Omar Mohammed ((Faculty of Arts Journal) مجلة كلية الآداب - جامعة مصراتة, 2016)
In a rapidly changing era marked by scientific and technological advancements, education faces significant challenges, including the need to equip educational supervisors with the necessary competencies. Given their crucial role in supporting teachers, this study highlights the low level of supervisory performance in Misrata and the unclear role of supervisors, largely due to a lack of essential supervisory skills. The research aims to assess these skills from the perspective of secondary school teachers, with the goal of enhancing effective practices and proposing training programs to address skill gaps.